Kajian Pengaruh Variasi Material Terhadap Kuat Tekan Beton - Suhendra Suhendra (Jurnal Civronlit Unbari, 2018)
Aggregate quality is very influential on the strength of the resulting concrete. Both coarse and fine aggregates have various characteristics identified from laboratory test results. This study aims to examine the use of various aggregates for a quality of concrete. The coarse aggregate and the fine aggregate used are obtained from the nearest location to the work to be performed. The quality of the concrete reviewed is K-125, K-175 and K-225. The coarse aggregates used are 1-2 size (in cm), 2-3 size (in cm) crushed aggregate and coral. The fine aggregates used for each of the coarse aggregates are also different. The results showed that the coral aggregate did not meet the gradations of concrete aggregate. While the fine aggregate does not meet the gradation of concrete aggregate for the three types used. The concrete compressive strength test results show the use of coarse aggregates of 2-3 size of crushed and coarse aggregate of corals giving the average compressive strength value required for all planned concrete strength. While concrete using coarse aggregates of rocks of size 1-2 only meet the specified compressive strength, but does not meet the required compressive strength.Key words: Aggregates, concrete, compressive strength